Optimalisasi Alokasi Penggunaan Lahan di Sub DAS Ambang: Pendekatan Analitikal Hirarki Proses dan Goal Programming (Optimalization of Land Use Planning in Ambang Sub-Watershed: Analytical Hierarchy Process and Goal Programming Approach) - Kresno Agus Hendarto (Jurnal Manajemen Hutan Tropika, 2008)
The purpose of land use planning on a river basin or a watershed is "to promote the accomplishment of service wide objectives and targets" subject to the lands potential and the public's desires. This paper aimed to describe a representative formulation of the analitical hierarchi process and linear programming application and show how it may be modified for goal programming. The purposive sampling was used to collect primary data. From five persons were represented each stakeholders on a watershed. The secondary data was collected from the report of each stakeholders and internet. The results show that goal programing had generated considerable interest as a tool for land use planning in multiple goal situations. It does present problems in terms of somewhat difficult data requirements-linearity in its usual form, possible inferior solutions, and lack of explicit recognition of tradeoffs.